Structure determination of the neutral exopolysaccharide produced by Lactobacillus delbrueckii subsp. bulgaricus OLL1073R-1. (2nd September 2015) - Van Calsteren, Marie-Rose; Gagnon, Fleur; Nishimura, Junko; Makino, Seiya
Abstract: The neutral exopolysaccharide (NPS) of Lactobacillus delbrueckii subsp. bulgaricus strain OLL1073R-1 was purified and characterized. The molecular mass was 5.0×10 6  g/mol. Sugar and absolute configuration analyses gave the following composition:d -Glc, 1;d -Gal, 1.5. The NPS was also submitted to periodate oxidation followed by borohydride reduction and Smith degradation. Sugar and methylation analyses, 1 H and 13 C nuclear magnetic resonance, and mass spectrometry of the NPS or of its specifically modified products allowed determining the repeating unit sequence: {2)Glc(α1–3)Glc(β1–3)[Gal(β1–4)]Gal(β1–4)Gal(α1–} n . The structure is compared to that of exopolysaccharides produced by other Lactobacillus bulgaricus strains. Graphical abstract: Highlights: Strain OLL1073R-1 produces a high-molecular-weight exopolysaccharide. The repeating unit is a branched pentasaccharide composed of Glc and Gal. The structure is compared to that of other strains of the same species.